Increasing Student's Speaking By Telling Short Story At The First Year Of SMP N 2 Bendosari Sukoharjo in 2011/2012 Academic Year - RISTYAWATI, DHIANA (2012)
The purpose of this research are to: (1) describ ing the implementation of telling short story to increase the students' speaking skill, (2) finding whether short story can improve speaking skill of the students, and (3) describ ing the students' response on the implementation of telling short story. The writer uses classroom action research. The subject of this classroom action research is the first year students of SMP Negeri 2 Bendosari in 2011/2012 academic year. The writer gets the data of this research from event, informant, and document. The events in this research are all of the activities occurred in the speaking class. Informants are the English teacher and the students of first year students of SMP N 2 Bendosari. Documents are all of the written information related to the interaction in speaking class. The method of collecting data is observation, interview, and test in speaking class. The results of the research show that (1) Telling short story can increase the students' speaking skill. (2) By telling short story, the students practice their speaking skill and increase their speaking skill. (3) The students give positive responses in teaching - learning speaking. Meanwhile, the problems faced by the students are lack of vocabulary, felt not confident with their ability, and felt difficult in speaking.